Agrometeorological Data and Rainfall Forecasting for Crop Simulation - AMIEN, LE ISTIQLAL; RUNTUNUWU, ELEONORA (Jurnal Sumberdaya Lahan, 2009)
Agricultural production is one of the most weather sensitive human activities that depend on daily atmospheric conditions. This review attempts to describe the meteorological data for crop requirements, some techniques of climate prediction and its use for crop simulations. Despite the rapid progress achieved in forecasting technology lately, further works are necessary for the real application. The amount and distribution of the rainfall in the coming season is necessary for planning crop cultivation particularly when climate anomaly arises. In agriculture the efforts to bridge the gap, climate forecasting results are the main input in crop simulation, especially for water and agro-climate management and cropping calendar.